Farm scale as a driver of agricultural development in the Kenyan Rift Valley. (January 2021) - Debonne, Niels; van Vliet, Jasper; Ramkat, Rose; Snelder, Denyse; Verburg, Peter
Abstract: Farming in Sub-Saharan Africa (SSA) is historically dominated by small-scale farms (SSFs), but evidence suggests that medium-scale farms (MSFs) are becoming increasingly prominent. These MSFs are often portrayed as entrepreneurial innovators, bringing dynamism and commercialization to SSA agriculture without displaying the negative features of land grabbing processes. However, there is little empirical evidence supporting these claims. We deployed a survey of 319 farmers covering a wide range of sizes in the Kenyan Rift Valley. Results show that MSFs are not a new phenomenon in the area, and are mostly farms that incrementally increased in size by buying or renting additional land. Furthermore, we find no differences in yields for various crop types between SSFs and MSFs. On average, MSFs use a higher share of their land for grazing, and have more dairy cattle per farm but less per hectare. The average MSF has a higher propensity to grow cash crops and serve non-local markets than the average SSF, and they employ significantly fewer people per hectare. However, within-category heterogeneity is high for all investigated dimensions, while past decision-making and future aspirations reveal entrepreneurship to occur in all farm size categories. We conclude that only a subset of all MSFs can be characterized as entrepreneurial, while these qualities can also be attached to many SSFs. Hence, we find that farm scale is an imperfect proxy to gauge the characteristics of a farm system, and presenting MSFs as a developmental panacea for SSA's rural areas is therefore unwarranted. Highlights: We compare medium-scale farms (MSF) with small-scale farms (SSF) in the Kenyan Rift Valley. MSF are not a new phenomenon, and most MSF have incrementally increased their farm size. On average, MSF produce more cash crops for non-local markets and use less labor. Farms do not differ in their average crop yields, but have different crop mixes. Average figures obfuscate large diversities within farm-size categories.